Stepped annular member
Patent Information
- Application Number
- JP2025059546
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0011】 本開示の段付き環状部材では、熱処理ひずみによる内径の変形量の軸方向におけるばらつきを十分に抑制できる。
Smart Images

Figure 2026166552000001_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a stepped annular member.
Background Art
[0002] Annular members such as gears used in automobiles and industrial machinery are repeatedly subjected to high stress. Therefore, these annular members are required to have high wear resistance and fatigue resistance. These annular members are usually manufactured by subjecting an intermediate product made of steel material to a predetermined heat treatment. The heat treatment performed in the manufacturing process of the annular member is, for example, carburizing and quenching treatment. In the carburizing and quenching treatment, after the annular member is heated to a temperature not lower than the austenite transformation temperature, carbon is permeated and diffused from the surface of the annular member to increase the carbon concentration in the surface layer. Thereafter, the annular member is rapidly cooled. As a result, a carburized layer having a high solid solution carbon concentration and mainly composed of a martensitic structure is formed on the surface layer of the annular member. The carburized layer is harder than the structure before the carburizing and quenching treatment. Therefore, the annular member having the carburized layer on the surface layer has improved wear resistance and fatigue resistance.
[0003] On the other hand, in the carburizing and quenching treatment, thermal stress due to temperature change and stress accompanying volume change due to phase transformation are generated in the annular member. As a result, strain is generated in the annular member, and the annular member is deformed. In the present specification, the deformation of the annular member caused by the carburizing and quenching treatment is referred to as heat treatment strain.
[0004] An annular member such as a gear used in automobiles or the like is generally fixed to a shaft or the like by inserting the shaft or the like so as to come into contact with the inner peripheral surface of the annular member. Therefore, when the inner diameter of the annular member is deformed under the influence of heat treatment strain, it is necessary to grind the inner peripheral surface to a predetermined dimension so that the inner diameter in the axial direction becomes constant. In this case, the manufacturing cost and construction period of the annular member increase. Furthermore, when the variation in the deformation amount of the inner diameter in the axial direction of the annular member is large, the removal amount of the carburized layer by grinding the inner peripheral surface also varies. As a result, variation in hardness occurs on the inner peripheral surface of the annular member, and the wear resistance and fatigue resistance are significantly reduced. Therefore, a technique for reducing the heat treatment strain of the annular member is demanded.
[0005] A technique for reducing heat treatment distortion of annular members is proposed, for example, in Japanese Patent Publication No. 2019-143211 (Patent Document 1). Patent Document 1 discloses an annular gear made of steel with a through hole formed therein for fixing a shaft. This annular gear comprises a cylindrical portion having a pair of annular end faces provided at both ends in the axial direction of the through hole, an inner circumferential surface connecting the inner edges of the pair of end faces, and an outer circumferential surface connecting the outer edges of the pair of end faces, and a plurality of teeth provided on the outer circumferential surface of the cylindrical portion, and the hardness of each pair of end faces is 300 HV or more lower than the hardness of the inner circumferential surface and the outer circumferential surface. Patent Document 1 states that this makes it possible to suppress large differences in the inner diameter depending on the position in the axial direction. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2019-143211 [Overview of the project] [Problems that the invention aims to solve]
[0007] Incidentally, annular members may have a stepped shape in which a thin-walled annular portion and a thick-walled annular portion with a greater wall thickness than the thin-walled portion are arranged along the axial direction. In this specification, such annular members with a stepped shape are referred to as stepped annular members. Compared to annular members with a constant wall thickness along the axial direction, stepped annular members tend to have greater axial variation in the amount of deformation of the inner diameter due to heat treatment strain. Therefore, in stepped annular members, it is necessary to further suppress heat treatment strain. However, Patent Document 1 does not consider suppressing heat treatment strain in stepped annular members at all.
[0008] The object of this disclosure is to provide a stepped annular member that can sufficiently suppress variations in the axial direction of the deformation amount of the inner diameter due to heat treatment strain. [Means for solving the problem]
[0009] The stepped annular member of this disclosure is The annular member body comprises an annular thin-walled portion having a wall thickness t1 (mm), and an annular thick-walled portion having a wall thickness t2 (mm) that is coaxial with and in contact with the thin-walled portion and is greater than 1 to 3 times the wall thickness t1, and having a constant inner diameter in the axial direction. The aforementioned member body further, The carburized layer formed on the surface, The region is located inside the carburized layer and includes a core where the total area ratio of the hard structure consisting of martensite and / or bainite is 95% or more. The chemical composition of the core is, in mass%, C: 0.10~0.20%, Si: 0.10~0.80%, Mn: 0.30~2.00%, P: 0.050% or less, S: 0.050% or less, Cr: 0.01~1.50%, Al: 0.010~0.100%, N: 0.005~0.030%, and, Contains O: 0.0030% or less, The remainder consists of Fe and impurities. Satisfying equation (1), At the axial center of the thickened portion, which is located at a depth of t2 / 2 (mm) radially from the inner circumferential surface, the area ratio of the hard tissue blocks with a short-axis width of 2.0 μm or more is 30 to 75%. 3.00 <Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in equation (1).
[0010] The stepped annular member of this disclosure is The annular member body comprises an annular thin-walled portion having a wall thickness t1 (mm), and an annular thick-walled portion having a wall thickness t2 (mm) that is coaxial with and in contact with the thin-walled portion and is greater than 1 to 3 times the wall thickness t1, and having a constant inner diameter in the axial direction. The member main body further comprises: a carburized layer formed on the surface layer, a core portion which is a region inside the carburized layer and has a total area fraction of a hard structure composed of martensite and / or bainite of 95% or more, The chemical composition of the core portion, in mass %, is: C: 0.10 to 0.20%, Si: 0.10 to 0.80%, Mn: 0.30 to 2.00%, P: 0.050% or less, S: 0.050% or less, Cr: 0.01 to 1.50%, Al: 0.010 to 0.100%, N: 0.005 to 0.030%, and O: 0.0030% or less, further containing one or more selected from the group consisting of Group 1 to Group 3, with the balance being Fe and impurities, and satisfying formula (1), At a center position of the thick portion, which is the axially central position of the thick portion and is located at a depth of t2 / 2 (mm) in the radial direction from the inner peripheral surface, the area fraction of the hard structure blocks having a minor axis width of 2.0 μm or more is 30 to 75%. [Group 1] Mo: 0.50% or less, Ti: 0.005% or less, Nb: 0.005% or less, V: 0.15% or less, and B: 0.0050% or less, one or more selected from the group consisting of the above elements [Group 2] Cu: 0.40% or less, Ni: 0.30% or less, and Sn: 0.100% or less, one or more selected from the group consisting of the above elements [Group 3] Ca: 0.0050% or less, and Mg: 0.0050% or less, one or more selected from the group consisting of the above elements 3.00<Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in Formula (1). [Effects of the Invention]
[0011] In the stepped annular member of the present disclosure, the axial variation in the deformation amount of the inner diameter caused by heat treatment strain can be sufficiently suppressed. [Brief Description of the Drawings]
[0012] [Figure 1] Figure 1 is a diagram showing the relationship between the area ratio (%) of hard structure blocks with a minor axis width of 2.0 μm or more at the center position of the thick portion of the stepped annular member, and the variation (mm) in inner diameter deformation amount due to heat treatment strain. [Figure 2] Figure 2 is a perspective view of the stepped annular member of the present embodiment. [Figure 3] Figure 3 is a plan view of the stepped annular member of the present embodiment. [Figure 4] Figure 4 is a plan view of a stepped annular member including a member main body having an inner peripheral surface subjected to spline processing. [Figure 5] Figure 5 is a vertical cross-sectional view including the central axis of the stepped annular member of the present embodiment. [Figure 6] Figure 6 is a transverse cross-sectional view of the thin portion of the stepped annular member of the present embodiment. [Figure 7] Figure 7 is a transverse cross-sectional view of the thin portion with a plurality of teeth formed on the outer periphery. [Modes for Carrying Out the Invention]
[0013] The present inventors conducted various studies on means for sufficiently suppressing the axial variation in the deformation amount of the inner diameter caused by heat treatment strain in a stepped annular member. Here, the stepped annular member includes a thin portion having a wall thickness t1 (mm) and a thick portion having a wall thickness t2 (mm) that is more than 1 time to 3 times the wall thickness t1, and is provided with an annular member main body having a constant inner diameter in the axial direction.
[0014] One of the factors causing variations in internal diameter deformation due to heat treatment strain is volume change due to phase transformation. Therefore, the inventors considered that it might be possible to suppress variations in internal diameter deformation due to heat treatment strain by adjusting the hardenability of the member body. So, the inventors first focused on the chemical composition of the core region, which is the area inside the carburized layer in a member body with a carburized layer formed on the surface, and conducted an investigation. As a result, the chemical composition of the core was as follows (by mass%): C: 0.10-0.20%, Si: 0.10-0.80%, Mn: 0.30-2.00%, P: 0.050% or less, S: 0.050% or less, Cr: 0.01-1.50%, Al: 0.010-0.100%, N: 0.005-0.030%, O: 0.0030% or less, Mo: 0-0.50%, Ti: 0-0.005%, Nb: 0-0. It was considered that if the material contains 0.005%, V: 0-0.15%, B: 0-0.0050%, Cu: 0-0.40%, Ni: 0-0.30%, Sn: 0-0.100%, Ca: 0-0.0050%, and Mg: 0-0.0050%, with the remainder being Fe and impurities, and satisfies the following formula (1), then the hardenability of the main body of the component is appropriate, and variations in the amount of internal diameter deformation due to heat treatment strain can be suppressed. 3.00 <Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in equation (1).
[0015] Formula (1) is an index for adjusting the hardenability of the component body. Mn and Cr contained in the component body enhance the hardenability of the component body. By adjusting the content of Mn and Cr in the chemical composition of the core to satisfy formula (1), the hardenability of the component body can be brought within an appropriate range. As a result of the inventors' investigations, it was found that when the chemical composition of the core satisfies formula (1), the variation in the amount of inner diameter deformation due to heat treatment strain can be sufficiently suppressed.
[0016] Therefore, the inventors further investigated the difference between cases where the variation in the amount of inner diameter deformation due to heat treatment strain was sufficiently suppressed and cases where it was not sufficiently suppressed in a stepped annular member whose core chemical composition satisfies formula (1). When the core chemical composition satisfies formula (1), the total area ratio of hard structures consisting of martensite and / or bainite in the microstructure of the core is 95% or more. In other words, the microstructure of the core consists mainly of hard structures. Here, the inventors focused on the size of the hard structure blocks. A hard structure block is a region in which prior austenite grains are partitioned by large-angle grain boundaries with an orientation difference of 15° or more.
[0017] Figure 1 shows the relationship between the area percentage (%) of hard tissue blocks with a short-axis width of 2.0 μm or more at the center of the thick-walled portion included in the core, and the variation in the amount of internal diameter deformation due to heat treatment strain (mm). In this specification, the area percentage of hard tissue blocks with a short-axis width of 2.0 μm or more at the center of the thick-walled portion is also referred to as the large block area percentage AR. Figure 1 was prepared using the results of test numbers from the examples described later, in which the core portion had the above-mentioned chemical composition and satisfied formula (1). As shown in Figure 1, in all stepped annular members where the variation in the amount of internal diameter deformation was sufficiently suppressed to 0.035 mm or less, the large block area percentage AR was 30-75%. On the other hand, in all stepped annular members where the variation in the amount of internal diameter deformation exceeded 0.035 mm, the large block area percentage AR was less than 30% or greater than 75%.
[0018] Based on the above findings, the inventors have discovered that in a stepped annular member in which the member body has the stepped shape described above and the core portion has the chemical composition described above, if the large block area ratio AR is 30 to 75%, then the axial variation in the amount of deformation of the inner diameter due to heat treatment strain is sufficiently suppressed. However, the mechanism by which the variation in the amount of deformation of the inner diameter is suppressed by having these configurations in a stepped annular member has not yet been elucidated. Nevertheless, it has been demonstrated by the embodiments described later that in a stepped annular member having the member body of the shape described above, the variation in the amount of deformation of the inner diameter can be suppressed by setting the chemical composition of the core portion within the above range and the large block area ratio AR to 30 to 75%.
[0019] The stepped annular member of this embodiment was completed based on the above technical concept and has the following configuration.
[0020] The stepped annular member of the first configuration is The annular member body comprises an annular thin-walled portion having a wall thickness t1 (mm), and an annular thick-walled portion having a wall thickness t2 (mm) that is coaxial with and in contact with the thin-walled portion and is greater than 1 to 3 times the wall thickness t1, and having a constant inner diameter in the axial direction. The aforementioned member body further, The carburized layer formed on the surface, The region is located inside the carburized layer and includes a core where the total area ratio of the hard structure consisting of martensite and / or bainite is 95% or more. The chemical composition of the core is, in mass%, C: 0.10~0.20%, Si: 0.10~0.80%, Mn: 0.30~2.00%, P: 0.050% or less, S: 0.050% or less, Cr: 0.01~1.50%, Al: 0.010~0.100%, N: 0.005~0.030%, and, Contains O: 0.0030% or less, The remainder consists of Fe and impurities. Satisfying equation (1), At the axial center of the thickened portion, which is located at a depth of t2 / 2 (mm) radially from the inner circumferential surface, the area ratio of the hard tissue blocks with a short-axis width of 2.0 μm or more is 30 to 75%. 3.00 <Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in equation (1).
[0021] The stepped annular member of the second configuration is The annular member body comprises an annular thin-walled portion having a wall thickness t1 (mm), and an annular thick-walled portion having a wall thickness t2 (mm) that is coaxial with and in contact with the thin-walled portion and is greater than 1 to 3 times the wall thickness t1, and having a constant inner diameter in the axial direction. The aforementioned member body further, The carburized layer formed on the surface, The region is located inside the carburized layer and includes a core where the total area ratio of the hard structure consisting of martensite and / or bainite is 95% or more. The chemical composition of the core is, in mass%, C: 0.10~0.20%, Si: 0.10~0.80%, Mn: 0.30~2.00%, P: 0.050% or less, S: 0.050% or less, Cr: 0.01~1.50%, Al: 0.010~0.100%, N: 0.005~0.030%, and, Contains O: 0.0030% or less, Furthermore, it contains one or more substances selected from the groups consisting of Group 1 to Group 3, The remainder consists of Fe and impurities. Satisfying equation (1), At the axial center of the thickened portion, which is located at a depth of t2 / 2 (mm) radially from the inner circumferential surface, the area ratio of the hard tissue blocks with a short-axis width of 2.0 μm or more is 30 to 75%. [Group 1] Mo: 0.50% or less Ti: 0.005% or less, Nb: 0.005% or less, V: 0.15% or less, and, B: Select one or more from the group consisting of 0.0050% or less. [Group 2] Cu: 0.40% or less, Ni: 0.30% or less, and, One or more selected from the group consisting of Sn: 0.100% or less. [Group 3] Ca: 0.0050% or less, One or more selected from the group consisting of Mg: 0.0050% or less. 3.00 <Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in equation (1).
[0022] The stepped annular member of the third configuration is A stepped annular member of the second configuration, The chemical composition of the core contains the first group.
[0023] The stepped annular member of the fourth configuration is A stepped annular member having a second or third configuration, The chemical composition of the core contains the second group.
[0024] A fifth configuration is a stepped annular member, A stepped annular member having one of the second to fourth configurations, The chemical composition of the core contains the third group.
[0025] The stepped annular member of the sixth configuration is A stepped annular member having one of the first to fifth configurations, Multiple teeth are formed on at least one of the outer circumferential surfaces of the thin-walled portion and the thick-walled portion, along the circumferential direction of the thin-walled portion or the thick-walled portion.
[0026] The stepped annular member of the seventh configuration is A stepped annular member having one of the configurations 1 to 6, A spline groove, keyway, or screw groove is formed on the inner circumferential surface of the member body.
[0027] The stepped annular member of this embodiment will be described in detail below. Unless otherwise specified, the "%" in relation to elements refers to "mass%".
[0028] [Shape of stepped annular member] Figure 2 is a perspective view of the stepped annular member 100 of this embodiment. In this specification, the direction parallel to the central axis X of the stepped annular member 100 is defined as the axial direction, the direction perpendicular to the central axis X is defined as the radial direction, and the circumferential direction of a circle centered on the central axis X is defined as the circumferential direction. In this specification, the cross section obtained when cut by a plane containing the central axis X is defined as the longitudinal section, and the cross section obtained when cut by a plane perpendicular to the central axis X is defined as the transverse section.
[0029] Referring to Figure 2, the stepped annular member 100 comprises a member body 30. The member body 30 is an annular shape with central axis X as its central axis. The member body 30 has a through hole and includes an inner circumferential surface 31. Figure 3 is a plan view of the stepped annular member 100 of this embodiment. The inner circumferential surface 31 may be a smooth circular surface. In this case, the inner circumferential surface 31 is circular when the member body 30 is viewed from above. The diameter of the inner circumferential surface 31 when the member body 30 is viewed from above is defined as the inner diameter dI (mm). The inner diameter dI of the member body 30 is constant in the axial direction. Half the value of the inner diameter dI of the member body 30 is defined as the inner radius rI (mm) of the member body 30.
[0030] Figure 4 is a plan view of the stepped annular member 100A of this embodiment, which has a different inner surface shape from the stepped annular member 100 described above. The inner surface 31 of the stepped annular member 100A is splined. In this embodiment, the inner surface 31 may be splined, keywayed, or threaded to form irregularities. In other words, spline teeth, keyways, or threads may be formed on the inner surface 31. In these cases, the minimum diameter of the inner surface 31 when the member body 30 is viewed from above is defined as the inner diameter dI of the member body 30. For example, if the inner surface 31 is splined, the smallest diameter of the spline hole as defined in JIS B 1603:1995 is defined as the inner diameter dI of the member body 30. Specifically, as shown in Figure 4, the diameter of the virtual cylinder in contact with the portion of the inner surface 31 where no spline grooves are formed is defined as the inner diameter dI of the member body 30. Similarly, if a keyway is machined on the inner circumferential surface 31, the diameter of the virtual cylinder in contact with the portion of the inner circumferential surface 31 where the keyway is not formed is defined as the inner diameter dI of the member body 30. If threads are cut on the inner circumferential surface 31, the diameter of the virtual cylinder in contact with the threads formed on the inner circumferential surface 31 is defined as the inner diameter dI of the member body 30.
[0031] Figure 5 is a longitudinal cross-sectional view of the stepped annular member 100. The longitudinal cross-section of the stepped annular member 100 is symmetrical with respect to the central axis X, and is arranged in two spaced apart on either side of the central axis X. In Figure 5, only one of the longitudinal cross-sections of the stepped annular member 100, on either side of the central axis X, is shown. Referring to Figures 2 and 5, the member body 30 includes a thin-walled portion 10 and a thick-walled portion 20. Specifically, the member body 30 is divided into a thin-walled portion 10 and a thick-walled portion 20 in the cross-section 33.
[0032] The thin-walled portion 10 is a part of the member body 30 and is a region demarcated by the cross-section 33 of the member body 30. The thin-walled portion 10 is an annular shape with the central axis X as its central axis. The thin-walled portion 10 includes an inner circumferential surface 11, which is a part of the inner circumferential surface 31 of the member body 30, and an outer circumferential surface 12. The inner circumferential surface 11 is a part of the inner circumferential surface 31. Therefore, the inner diameter dI of the thin-walled portion 10 is constant in the axial direction.
[0033] Figure 6 is a cross-sectional view of the thin-walled portion 10 in the stepped annular member 100 of this embodiment. In this embodiment, the shape of the outer circumferential surface 12 in the cross-section of the thin-walled portion 10 may be circular, as shown in Figure 6. In this case, the radius of the outer circumferential surface 12 is defined as the outer radius rO1 (mm). Figure 7 is a cross-sectional view of the thin-walled portion 10 in the stepped annular member 100B of this embodiment, which has a different outer circumferential surface shape from the stepped annular member 100 and stepped annular member 100A described above. In this embodiment, as shown in Figure 7, a plurality of teeth 14 may be formed on the outer circumferential surface 12 of the thin-walled portion 10 along the circumferential direction of the thin-walled portion 10. That is, when a plurality of teeth 14 are formed on the outer circumferential surface 12 of the thin-walled portion 10, the shape of the outer circumferential surface 12 in the cross-section of the thin-walled portion 10 does not have to be circular. In this case, the radial distance from the central axis X to the tooth root 15 is defined as the outer radius rO1 (mm). In the thin-walled section 10, the difference between the outer radius rO1 (mm) and the inner radius rI (mm) is defined as the wall thickness t1 (mm) of the thin-walled section 10. Regardless of the presence or absence of multiple teeth 14, the wall thickness t1 of the thin-walled section 10 is constant in the axial direction.
[0034] Let the axial length of the thin-walled portion 10 be h1 (mm). The axial length h1 of the thin-walled portion 10 is not particularly limited. The lower limit of the ratio of the axial length h1 to the wall thickness t1 is, for example, 0.20, 0.40, 0.60, 0.80, and 1.00. The upper limit of the ratio of the axial length h1 of the thin-walled portion 10 to the wall thickness t1 is, for example, 10.00, 8.00, 6.00, 4.00, and 3.00.
[0035] The thickened portion 20 is a part of the member body 30 and is a region demarcated by the cross-section 33 of the member body 30. The thickened portion 20 is an annular shape with the central axis X as its central axis. In other words, the thickened portion 20 is arranged coaxially with the thinned portion 10. The thickened portion 20 is further arranged in contact with the thinned portion 10. The thickened portion 20 includes an inner circumferential surface 21, which is part of the inner circumferential surface 31 of the member body 30, and an outer circumferential surface 22. The inner circumferential surface 21 is part of the inner circumferential surface 31. Therefore, the inner diameter dI of the thickened portion 20 is constant in the axial direction.
[0036] In this embodiment, the thick-walled portion 20 may have a circular outer surface 22 in its cross-section, similar to the thin-walled portion 10, or multiple teeth may be formed on the outer surface 22 of the thick-walled portion 20 along the circumferential direction of the thick-walled portion 20. In other words, if multiple teeth are formed on the outer surface 22 of the thick-walled portion 20, the shape of the outer surface 22 in its cross-section does not have to be circular. If the shape of the outer surface 22 in the cross-section of the thick-walled portion 20 is circular, the radius of the outer surface 22 is defined as the outer radius rO2 (mm). If the shape of the outer surface 22 in the cross-section of the thick-walled portion 20 is not circular and multiple teeth are formed on the outer surface 22 of the thick-walled portion 20, the radial distance from the central axis X to the tooth root is defined as the outer radius rO2 (mm). In the thick-walled portion 20, the difference between the outer radius rO2 (mm) and the inner radius rI (mm) is defined as the wall thickness t2 (mm) of the thick-walled portion 20. Regardless of the presence or absence of multiple teeth, the thickness t2 of the thickened portion 20 is constant in the axial direction.
[0037] The wall thickness t2 (mm) of the thick-walled portion 20 is more than 1 to 3 times the wall thickness t1 (mm) of the thin-walled portion 10. The preferred lower limit of the ratio of wall thickness t2 (mm) to wall thickness t1 (mm) is 1.1, more preferably 1.5, and even more preferably 1.8. The preferred upper limit of the ratio of wall thickness t2 (mm) to wall thickness t1 (mm) is less than 3, more preferably 2.9, even more preferably 2.6, even more preferably 2.3, and even more preferably 2.1.
[0038] The axial length of the thickened portion 20 is defined as h2 (mm). The axial length h2 of the thickened portion 20 is not particularly limited. The lower limit of the ratio of the axial length h2 to the thickness t2 is, for example, 0.10, 0.15, 0.20, 0.25, 0.30, and 0.33. The upper limit of the ratio of the axial length h2 to the thickness t2 is, for example, 5.00, 4.50, 4.00, 3.50, and 3.00. Furthermore, the axial center position of the thickened portion 20, located at a depth of t2 / 2 (mm) radially from the inner circumferential surface 21, is defined as the center position 23 of the thickened portion. The center position 23 of the thickened portion is included in the core portion 50, which will be described later.
[0039] [Carburized layer] Referring to Figure 5, a carburized layer 40 is formed on the surface of the member body 30. The carburized layer 40 is a region where carbon penetrates from the surface due to the carburizing and quenching treatment, and the solid solution carbon concentration is higher compared to the structure before the carburizing and quenching treatment. The microstructure of the carburized layer 40 consists mainly of martensite. Here, if the carbon concentration by mass is 0.60% or higher at a depth of 100 μm from the surface of the member body 30, it is determined that the carburized layer 40 is formed on the surface of the member body 30.
[0040] [Method for measuring carbon concentration at a depth of 100 μm from the surface] The carbon concentration at a depth of 100 μm from the surface of the component body 30 is determined using an electron probe microanalyzer (EPMA). Specifically, a test specimen is taken from the stepped annular member 100, with the observation surface including a depth of 100 μm from the surface of the component body 30. The size of the test specimen is not particularly limited, as long as the observation surface includes a 50 μm × 50 μm measurement area with the 100 μm depth position at its center. The observation surface is parallel to the radial direction. The carbon concentration (mass%) is measured on the observation surface of the obtained test specimen using EPMA. Specifically, surface analysis is performed on the measurement area of the observation surface as described above. The arithmetic mean of the carbon concentration (mass%) in the obtained measurement area is defined as the carbon concentration (mass%) at a depth of 100 μm from the surface of the component body 30. For the EPMA surface analysis, the acceleration voltage is set to 15 kV, the irradiation current to 500 nA, the electron beam diameter to 3 μm, and the measurement pitch to 3 μm.
[0041] [Core] Referring to Figure 5, the region inside the carburized layer 40 in the member body 30 is defined as the core 50. The core 50 is the region that is not affected by the intrusion and diffusion of carbon due to the carburizing and quenching process.
[0042] [Microstructure of the core] The core 50 has a total area ratio of 95% or more of hard tissue consisting of martensite and / or bainite. In other words, the core 50 is mainly composed of hard tissue. Other tissues in the microstructure of the core 50 besides martensite and bainite include, for example, ferrite, pearlite, carbides, and retained austenite.
[0043] [Method for measuring the microstructure of the core] The total area ratio of the hard tissue in the core 50 is determined by the following method. First, the total area ratio of ferrite and pearlite in the core portion 50 is determined. A test piece is taken from the main body 30 of the component, including a surface perpendicular to the axial direction as the observation surface. The observation surface includes a measurement area of 1 mm × 1 mm centered on the center position 23 of the thickened portion. The observation surface is mirror-polished. Etching is performed on the mirror-polished observation surface using 2% nitric acid alcohol (Nital etching solution). Of the etched observation surface, five arbitrary observation fields (240 μm × 180 μm) within the measurement area are observed with a 500x optical microscope. In the 500x observation field, the hard structure and ferrite and pearlite can be easily distinguished by contrast, etc. Specifically, the hard structure is observed as a phase containing substructures (lath). Ferrite does not show substructures within the grains and is observed as a region with higher brightness than the hard structure. Furthermore, because pearlite has a lamellar structure and is more strongly corroded by Nital etching solution than hard tissue, it is observed as a region with lower brightness than hard tissue. The total area of ferrite and pearlite in the observation field is determined by known image processing. The total area ratio of ferrite and pearlite is determined based on the total area of ferrite and pearlite identified in all observation fields and the total area of all observation fields.
[0044] Next, the area ratio of carbides in the core portion 50 is determined. A test piece is taken from the main body 30 of the member, including a surface perpendicular to the axial direction as the observation surface. The observation surface includes a measurement area of 1 mm × 1 mm centered on the center position 23 of the thickened portion. The observation surface is mirror-polished. From the mirror-polished observation surface, five arbitrary observation fields (240 μm × 180 μm) within the measurement area are observed with a field emission scanning electron microscope (FE-SEM) and Z-contrast images, also known as COMPO images, are captured from the backscattered electron detector. The observation magnification is set to 500x. All carbides with an equivalent circle diameter of 5 μm or more are identified from the captured photographic images. Here, the equivalent circle diameter refers to the diameter (μm) when the area of the carbide is converted to a circle. Carbides with an equivalent circle diameter of less than 5 μm can be ignored as they are part of martensite and bainite. Furthermore, in contrast images, martensitic and bainite structures, which are mainly composed of iron, can be easily distinguished from carbides, which contain a large amount of carbon. The area ratio of carbides is defined as the area ratio calculated based on the total area of carbides with an equivalent circle diameter of 5 μm or more identified in all observation fields and the total area of all observation fields.
[0045] Furthermore, the area ratio of retained austenite in the core portion 50 is determined. A test specimen is taken from the member body 30, including a plane perpendicular to the axial direction as the measurement surface. The measurement surface includes the center position 23 of the thickened portion. X-ray diffraction measurement is performed on the measurement surface of the obtained test specimen. Specifically, X-rays are irradiated onto the center position 23 of the thickened portion of the measurement surface, and the X-ray diffraction intensity of each of the α-phase (110) plane, α-phase (200) plane, α-phase (211) plane, α-phase (220) plane, γ-phase (200) plane, and γ-phase (311) plane is measured, and the integrated intensity of each plane is calculated. In measuring the X-ray diffraction intensity, the target of the X-ray diffractometer is set to Cu (CuKα rays), and the output is set to 40kV-400mA. After calculation, the volume fraction Vγ (%) of retained austenite is calculated for each combination (4 × 3 = 12 pairs) of each face of the α phase and each face of the γ phase using equation (I). The average value of the volume fraction Vγ of the 12 pairs of retained austenite is then defined as the area fraction (%) of retained austenite. Vγ=100 / {1+(Iα×Rγ) / (Iγ×Rα)} (I) Here, Iα is the integrated intensity of the α phase. Rα is the crystallographic theoretical calculation value of the α phase. Iγ is the integrated intensity of the γ phase. Rγ is the crystallographic theoretical calculation value of the γ phase. In this specification, Rα at the (110) plane of the α phase is set to 100, Rα at the (200) plane of the α phase is set to 14.0, Rα at the (211) plane of the α phase is set to 25.6, Rα at the (220) plane of the α phase is set to 8.4, Rγ at the (200) plane of the γ phase is set to 34.0, Rγ at the (220) plane of the γ phase is set to 17.9, and Rγ at the (311) plane of the γ phase is set to 20.5.
[0046] Finally, the total area percentage (%) of the hard tissue in the core 50 is calculated using the following formula. Total area percentage of hard tissue (%) = 100 - (Total area percentage of ferrite and pearlite (%) + Area percentage of carbides (%) + Area percentage of retained austenite (%))
[0047] [Chemical composition of the core] The chemical composition of the core 50 contains the following elements:
[0048] C: 0.10~0.20% Carbon (C) increases the strength of the stepped annular member 100. If the C content is less than 0.10%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the carbon content exceeds 0.20%, even if the content of other elements is within the range of this embodiment, the hardness of the steel material used for the stepped annular member 100 will become excessively high. As a result, the workability of the steel material will decrease. Therefore, the C content is 0.10-0.20%. The preferred lower limit for the C content is 0.11%, more preferably 0.13%, and even more preferably 0.15%. The preferred upper limit for the C content is 0.19%, more preferably 0.17%, and even more preferably 0.15%.
[0049] Si: 0.10~0.80% Silicon (Si) deoxidizes steel during the steelmaking process. If the Si content is 0.10% or less, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Si content exceeds 0.80%, the workability of the steel material used for the stepped annular member 100 will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Si content is 0.10-0.80%. The preferred lower limit for the Si content is 0.15%, more preferably 0.20%, and even more preferably 0.25%. The preferred upper limit for the Si content is 0.75%, more preferably 0.70%, and even more preferably 0.65%.
[0050] Mn: 0.30~2.00% Manganese (Mn) enhances hardenability and increases the strength of the stepped annular member 100. If the Mn content is less than 0.30%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Mn content exceeds 2.00%, the workability of the steel material used for the stepped annular member 100 will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Mn content is 0.30-2.00%. The preferred lower limit for the Mn content is 0.35%, more preferably 0.40%, and even more preferably 0.45%. The preferred upper limit for the Mn content is 1.80%, more preferably 1.50%, and even more preferably 1.20%.
[0051] P:0.050% or less Phosphorus (P) is an impurity. If the P content exceeds 0.050%, P will excessively segregate at the grain boundaries, reducing the grain boundary strength. As a result, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 will decrease. Therefore, the P content is 0.050% or less. A low phosphorus (P) content is preferable. However, excessive reduction of the P content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the P content is greater than 0%, more preferably 0.001%, even more preferably 0.002%, and even more preferably 0.003%. The preferred upper limit for the P content is 0.045%, more preferably 0.040%, even more preferably 0.035%, and even more preferably 0.030%.
[0052] S: 0.050% or less Sulfur (S) is an impurity. If the S content exceeds 0.050%, coarse sulfide inclusions will form. As a result, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 will decrease. Therefore, the sulfur content is 0.050% or less. A low sulfur (S) content is preferable. However, excessive reduction of the S content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the S content is greater than 0%, more preferably 0.001%, and even more preferably 0.002%. The preferred upper limit for the S content is 0.045%, more preferably 0.040%, even more preferably 0.035%, and even more preferably 0.030%.
[0053] Cr: 0.01~1.50% Chromium (Cr) enhances hardenability and increases the strength of the stepped annular member 100. If the Cr content is less than 0.01%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Cr content exceeds 1.50%, the workability of the steel material used for the stepped annular member 100 will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Cr content is between 0.01% and 1.50%. The preferred lower limit for the Cr content is 0.03%, more preferably 0.05%, and even more preferably 0.07%. The preferred upper limit for the Cr content is 1.30%, more preferably 1.10%, and even more preferably 0.90%.
[0054] Al: 0.010~0.100% Aluminum (Al) combines with nitrogen to form AlN, and the pinning effect suppresses grain coarsening during heating in the carburizing process. As a result, the toughness of the stepped annular member 100 is increased. If the Al content is less than 0.010%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Al content exceeds 0.100%, coarse oxides are formed. As a result, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 decreases. Therefore, the Al content is between 0.010% and 0.100%. The preferred lower limit for the Al content is 0.015%, more preferably 0.020%, and even more preferably 0.025%. The preferred upper limit for the Al content is 0.090%, more preferably 0.080%, and even more preferably 0.070%.
[0055] N: 0.005~0.030% Nitrogen (N) combines with Ti, Al, V, and Nb in the steel to form nitrides and carbonitrides, and the pinning effect suppresses grain coarsening during heating in the carburizing and quenching process. As a result, the toughness of the stepped annular member 100 is increased. If the N content is less than 0.005%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the N content exceeds 0.030%, coarse nitrides are formed. As a result, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 decreases. Therefore, the N content is 0.005 to 0.030%. The preferred lower limit for the N content is 0.007%, more preferably 0.009%, and even more preferably 0.011%. The preferred upper limit for the N content is 0.028%, more preferably 0.026%, and even more preferably 0.020%.
[0056] O: 0.0030% or less Oxygen (O) is an impurity. O combines with other elements to form coarse oxide inclusions. If the O content exceeds 0.0030%, the toughness of the stepped annular member 100 will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the O content is 0.0030% or less. A low oxygen content is preferable. However, excessive reduction of the oxygen content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the oxygen content is greater than 0%, more preferably 0.0001%, even more preferably 0.0002%, and even more preferably 0.0003%. The preferred upper limit for the O content is 0.0028% or less, more preferably 0.0025%, and even more preferably 0.0020%.
[0057] The remainder of the chemical composition of the core portion 50 consists of Fe and impurities. Here, impurities in the chemical composition refer to substances that are mixed in from raw materials such as ore, scrap, or the manufacturing environment during the industrial production of the stepped annular member 100, and are acceptable within a range that does not adversely affect the stepped annular member 100 of this embodiment.
[0058] [About Optional Elements] The chemical composition of the core portion 50 may further include one or more elements selected from the groups consisting of Group 1 to Group 3, in place of a portion of the Fe. [Group 1] Mo: 0.50% or less Ti: 0.005% or less, Nb: 0.005% or less, V: 0.15% or less, and, B: Select one or more from the group consisting of 0.0050% or less. [Group 2] Cu: 0.40% or less, Ni: 0.30% or less, and, One or more selected from the group consisting of Sn: 0.100% or less. [Group 3] Ca: 0.0050% or less, One or more selected from the group consisting of Mg: 0.0050% or less. The following describes these arbitrary elements.
[0059] [Group 1: Mo, Ti, Nb, V, and B] The chemical composition of the core 50 may further include one or more elements selected from the group consisting of Mo, Ti, Nb, V, and B in place of some of the Fe. These elements are arbitrary and all increase the strength of the stepped annular member 100.
[0060] Mo: 0.50% or less Molybdenum (Mo) is an optional element and does not need to be included. In other words, the Mo content may be 0%. If Mo is present, that is, if the Mo content is greater than 0%, Mo increases the tempering softening resistance and enhances the strength of the stepped annular member 100. Even if only a small amount of Mo is present, the above effect can be obtained to some extent. On the other hand, if the Mo content exceeds 0.50%, the hardness of the steel material used for the stepped annular member 100 becomes excessively high. As a result, even if the content of other elements is within the range of this embodiment, the workability of the steel material decreases. Therefore, the Mo content is between 0 and 0.50%, and if present, the Mo content is 0.50% or less. The preferred lower limit for the Mo content is 0.01%, more preferably 0.02%, and even more preferably 0.03%. The preferred upper limit for the Mo content is 0.45%, more preferably 0.40%, and even more preferably 0.35%.
[0061] Ti: 0.005% or less Titanium (Ti) is an optional element and does not need to be included. In other words, the Ti content may be 0%. If Ti is present, that is, if the Ti content is greater than 0%, the Ti will form Ti precipitates such as Ti carbides and Ti carbonitrides. These Ti precipitates strengthen the stepped annular member 100 through precipitation strengthening. Even if only a small amount of Ti is present, the above effect can be obtained to some extent. On the other hand, if the Ti content exceeds 0.005%, the Ti precipitates become coarser. In this case, the coarsening of the crystal grains during the carburizing treatment cannot be sufficiently suppressed. Therefore, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 decreases. Therefore, the Ti content is 0-0.005%, and if present, the Ti content is 0.005% or less. The preferred lower limit for the Ti content is 0.001%, and more preferably 0.002%. The preferred upper limit for the Ti content is 0.004%, and more preferably 0.003%.
[0062] Nb: 0.005% or less Niobium (Nb) is an optional element and does not need to be included. In other words, the Nb content may be 0%. If Nb is present, that is, if the Nb content is greater than 0%, the Nb forms Nb precipitates such as Nb carbides and Nb carbonitrides. These Nb precipitates strengthen the stepped annular member 100 through precipitation. Even if only a small amount of Nb is present, the above effect can be obtained to some extent. On the other hand, if the Nb content exceeds 0.005%, the Nb precipitates become coarser. In this case, the coarsening of the crystal grains during the carburizing treatment cannot be sufficiently suppressed. Therefore, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 decreases. Therefore, the Nb content is 0-0.005%, and if present, the Nb content is 0.005% or less. The preferred lower limit for the Nb content is 0.001%, and more preferably 0.002%. The preferred upper limit for the Nb content is 0.004%, and more preferably 0.003%.
[0063] V: 0.15% or less Vanadium (V) is an optional element and may not be present. In other words, the V content may be 0%. If V is present, that is, if the V content is greater than 0%, V forms V precipitates such as V carbides and V carbonitrides. These V precipitates strengthen the stepped annular member 100 through precipitation. Even if only a small amount of V is present, the above effect can be obtained to some extent. On the other hand, if the V content exceeds 0.15%, the hardness of the steel material used for the stepped annular member 100 becomes excessively high. As a result, even if the content of other elements is within the range of this embodiment, the workability of the steel material decreases. Therefore, the V content is 0-0.15%, and if present, the V content is 0.15% or less. The preferred lower limit for the V content is 0.01%, more preferably 0.03%, and even more preferably 0.05%. The preferred upper limit for the V content is 0.13%, more preferably 0.11%, and even more preferably 0.09%.
[0064] B: 0.0050% or less Boron (B) is an optional element and does not need to be included. In other words, the B content may be 0%. If B is present, that is, if the B content is greater than 0%, B strengthens the stepped annular member 100 through solid solution strengthening. Even if only a small amount of B is present, the above effect can be obtained to some extent. On the other hand, if the B content exceeds 0.0050%, the hardness of the steel material used for the stepped annular member 100 becomes excessively high. As a result, even if the content of other elements is within the range of this embodiment, the workability of the steel material decreases. Therefore, the B content is 0-0.0050%, and if present, the B content is 0.0050% or less. The preferred lower limit for the B content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0005%. The preferred upper limit for the B content is 0.0045%, more preferably 0.0040%, and even more preferably 0.0035%.
[0065] [Group 2: Cu, Ni, and Sn] The chemical composition of the core 50 may further include one or more elements selected from the group consisting of Cu, Ni, and Sn in place of some of the Fe. These elements are arbitrary and all enhance the corrosion resistance of the stepped annular member 100.
[0066] Cu:0.40% or less Copper (Cu) is an optional element and does not need to be included. In other words, the Cu content may be 0%. If present, that is, if the Cu content is greater than 0%, Cu enhances the corrosion resistance of the stepped annular member 100. Even if only a small amount of Cu is present, the above effect can be obtained to some extent. On the other hand, if the Cu content exceeds 0.40%, the hardness of the steel material used for the stepped annular member 100 becomes excessively high. As a result, even if the content of other elements is within the range of this embodiment, the workability of the steel material decreases. Therefore, the Cu content is 0-0.40%, and if present, the Cu content is 0.40% or less. The preferred lower limit for the Cu content is 0.01%, more preferably 0.02%, and even more preferably 0.03%. The preferred upper limit for the Cu content is 0.35%, more preferably 0.30%, and even more preferably 0.25%.
[0067] Ni: 0.30% or less Nickel (Ni) is an optional element and does not need to be included. In other words, the Ni content may be 0%. If present, i.e., if the Ni content is greater than 0%, Ni enhances the corrosion resistance of the stepped annular member 100. Even if only a small amount of Ni is present, the above effect can be obtained to some extent. On the other hand, if the Ni content exceeds 0.30%, the hardness of the steel material used for the stepped annular member 100 becomes excessively high. As a result, even if the content of other elements is within the range of this embodiment, the workability of the steel material decreases. Therefore, the Ni content is 0-0.30%, and if present, the Ni content is 0.30% or less. The preferred lower limit for the Ni content is 0.01%, more preferably 0.02%, and even more preferably 0.03%. The preferred upper limit for the Ni content is 0.25%, more preferably 0.20%, and even more preferably 0.15%.
[0068] Sn: 0.100% or less Tin (Sn) is an optional element and does not need to be included. In other words, the Sn content may be 0%. If present, i.e., if the Sn content is greater than 0%, Sn enhances the corrosion resistance of the stepped annular member 100. Even if only a small amount of Sn is present, the above effect can be obtained to some extent. On the other hand, if the Sn content exceeds 0.100%, the hardness of the steel material used for the stepped annular member 100 becomes excessively high. As a result, even if the content of other elements is within the range of this embodiment, the workability of the steel material decreases. Therefore, the Sn content is between 0 and 0.100%, and if present, the Sn content is 0.100% or less. The preferred lower limit for the Sn content is 0.001%, more preferably 0.002%, and even more preferably 0.003%. The preferred upper limit for the Sn content is 0.090%, more preferably 0.070%, and even more preferably 0.050%.
[0069] [Group 3: Ca and Mg] The chemical composition of the core 50 may further include one or more elements selected from the group consisting of Ca and Mg in place of a portion of Fe. These elements are arbitrary and all improve the workability of the steel material that will be used to form the stepped annular member 100.
[0070] Ca:0.0050% or less Calcium (Ca) is an optional element and does not need to be included. In other words, the Ca content may be 0%. When calcium is present, that is, when the calcium content is greater than 0%, the calcium neutralizes sulfur in the steel by fixing it as sulfides, thereby improving the workability of the steel. Even a small amount of calcium can provide the above effect to some extent. On the other hand, if the Ca content exceeds 0.0050%, the oxides in the steel become coarser. Therefore, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 decreases. Therefore, the Ca content is between 0 and 0.0050%, and if present, the Ca content is 0.0050% or less. The preferred lower limit for the Ca content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%. The preferred upper limit for the Ca content is 0.0045%, more preferably 0.0040%, and even more preferably 0.0035%.
[0071] Mg: 0.0050% or less Magnesium (Mg) is an optional element and does not need to be included. In other words, the Mg content may be 0%. When magnesium is present, that is, when the Mg content is greater than 0%, the Mg neutralizes sulfur in the steel by fixing it as sulfides, thereby improving the workability of the steel. Even if only a small amount of Mg is present, the above effect can be obtained to some extent. On the other hand, if the Mg content exceeds 0.0050%, the oxides in the steel become coarser. Therefore, even if the content of other elements is within the range of this embodiment, the toughness of the stepped annular member 100 decreases. Therefore, the Mg content is between 0 and 0.0050%, and if present, the Mg content is 0.0050% or less. The preferred lower limit of the Mg content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%. The preferred upper limit for the Mg content is 0.0045%, more preferably 0.0040%, and even more preferably 0.0035%.
[0072] [Formula (1)] The chemical composition of the core 50 further satisfies formula (1). 3.00 <Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in equation (1).
[0073] Fn1 is defined as follows: Fn1 = Mn + 3.08Cr Fn1 is an index used to adjust the hardenability of the component body 30. The Mn and Cr contained in the component body 30 enhance its hardenability. In other words, the higher the Fn1, the higher the hardenability of the component body 30.
[0074] As described above, one of the factors causing variations in internal diameter deformation due to heat treatment strain is volume change due to phase transformation. When the hardenability of the member body 30 changes, the manner of phase transformation during heat treatment changes. As a result, the degree of variation in internal diameter deformation also changes. If Fn1 is 3.00 or less, the hardenability of the member body 30 is too low. In this case, the large block area ratio AR, which will be described later, becomes too high and cannot be adjusted to an appropriate range. As a result, variations in internal diameter deformation due to heat treatment strain cannot be sufficiently suppressed. If Fn1 is 5.00 or more, the hardenability of the member body 30 is too high. In this case, the large block area ratio AR becomes too low and cannot be adjusted to an appropriate range. As a result, variations in internal diameter deformation due to heat treatment strain cannot be sufficiently suppressed.
[0075] On the other hand, if Fn1 is greater than 3.00 and less than 5.00, the hardenability of the member body 30 is within an appropriate range. In this case, by appropriately adjusting the large block area ratio AR, the axial variation in the amount of inner diameter deformation due to heat treatment strain can be sufficiently suppressed. Therefore, in the stepped annular member 100 of this embodiment, the chemical composition of the core portion 50 satisfies formula (1). Note that Fn1 is the value obtained by rounding the third decimal place of the calculated value to two decimal places.
[0076] [Area ratio of hard tissue blocks with a short-axis width of 2.0 μm or more] In the stepped annular member 100 of this embodiment, the area ratio of hard tissue blocks with a short-axis width of 2.0 μm or more at the center position 23 of the thickened portion is 30 to 75%. As described above, in this specification, the area ratio of hard tissue blocks with a short-axis width of 2.0 μm or more at the center position 23 of the thickened portion is referred to as the large block area ratio AR. Furthermore, a hard tissue block is a region in which prior austenite grains are partitioned by large-angle grain boundaries with an orientation difference of 15° or more.
[0077] As shown in Figure 1, if the large block area ratio AR is 30-75%, assuming that the stepped annular member 100 has the above-described configuration, the axial variation in the amount of inner diameter deformation due to heat treatment strain is sufficiently suppressed. Therefore, in the stepped annular member 100 of this embodiment, the large block area ratio AR is set to 30-75%.
[0078] [Measurement method for the area ratio (AR) of large blocks] The large block area ratio (AR) is determined by the following method using electron backscatter diffraction (EBSD). Three test specimens are taken from the main body 30 of the component, each containing a surface perpendicular to the axial direction as the observation surface. Each observation surface includes a measurement area of 200 μm × 200 μm centered on the center position 23 of the thickened portion. The observation surfaces of the test specimens are electropolished. The applied voltage for electropolishing is 35 V, and the polishing time is 10 seconds. The electrolyte is a mixed solution of 78 mL of perchloric acid, 90 mL of distilled water, 730 mL of ethanol, and 100 mL of butyl cellosolve.
[0079] EBSD measurements are performed on the measurement area of each specimen. In the EBSD measurements, the acceleration voltage is set to 20kV and the irradiation current to 20nA or more, for example, 28nA. The observation magnification is set to 400x and the step size to 0.3μm. The measurement results in each measurement area are analyzed using well-known analysis software to obtain a crystal orientation map of the hard structure (bcc structure). A well-known analysis software is, for example, EDAX OIM Analysis, manufactured by AMETEK Corporation. In the crystal orientation map, boundaries where the orientation difference is 15° or more are defined as large-angle grain boundaries, and the area enclosed by large-angle grain boundaries is defined as a block of the hard structure. Furthermore, the shape of the hard structure block is approximated by an ellipse, and the minor axis of the obtained ellipse is defined as the minor axis width of the block. For example, in the above-mentioned EDAX OIM Analysis, the minor axis width of the hard structure block is analyzed and output as "Minor Axis". Hard structure blocks with a minor axis width of 2.0μm or more are identified and defined as large blocks. Furthermore, specific targets are limited to those in which the entire hard tissue block is included in the resulting crystal orientation map. In other words, hard tissue blocks that are partially outside the crystal orientation map are excluded from the selection of large blocks.
[0080] In each measurement area, the total area of all large blocks is determined. Based on the total area of each measurement area in the three test specimens and the total area of large blocks in each measurement area, the large block area ratio AR (%) is calculated. The large block area ratio AR is an integer value obtained by rounding the obtained value to the first decimal place.
[0081] [Application] In the stepped annular member 100 of this embodiment, variations in the axial direction of the deformation amount of the inner diameter due to heat treatment strain are sufficiently suppressed. Therefore, it is suitable as a carburized member such as a gear, into which a shaft or the like is inserted and fixed so as to contact the inner circumferential surface 31. On the other hand, the applications of the stepped annular member 100 of this embodiment are not limited to gears. Applications of the stepped annular member 100 of this embodiment other than gears include, for example, stepped shafts and shafts of different diameters.
[0082] [Manufacturing method] An example of a method for manufacturing the stepped annular member 100 of this embodiment includes the following steps. The method for manufacturing the stepped annular member 100 described below is an example for manufacturing the stepped annular member 100 of this embodiment. Therefore, the stepped annular member 100 having the above-described configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing the stepped annular member 100 of this embodiment.
[0083] An example of a method for manufacturing the stepped annular member 100 of this embodiment includes the following steps. (Process 1) Steel material preparation process (Process 2) Processing process (Step 3) Carburizing and quenching process (Process 4) Tempering process The following describes each step.
[0084] [(Process 1) Steel material preparation process] In the steel material preparation process, the steel material to be used for the stepped annular member 100 of this embodiment is prepared. Specifically, molten steel having a chemical composition that satisfies the above-mentioned range of elemental content and formula (1) is produced. The refining method is not particularly limited, and any well-known method may be used. For example, molten iron produced by a well-known method is subjected to refining in a converter (primary refining). A well-known secondary refining is performed on the molten steel tapped from the converter. In secondary refining, alloying elements are added to the molten steel to adjust the composition and produce molten steel having a chemical composition that satisfies the above-mentioned range of elemental content and formula (1).
[0085] Using the molten steel produced by the refining method described above, a material is manufactured by a well-known casting method. For example, an ingot may be manufactured using the ingot-making method with the molten steel. Alternatively, a bloom or billet may be manufactured using the continuous casting method with the molten steel. A well-known hot working method is performed on the manufactured casting material (ingot, bloom, or billet) to produce a steel material of a predetermined shape. For example, hot forging may be performed as part of the hot working. Alternatively, after performing bloc rolling or hot forging, finish rolling may be performed using a continuous rolling mill. The continuous rolling mill is equipped with multiple rolling stands arranged in a row. The heating temperature during hot working is not particularly limited, but is, for example, 1000 to 1300°C. The shape of the steel material manufactured in this way is, for example, a steel bar or wire.
[0086] In the example described above, hot working is performed on the manufactured casting to produce steel. However, in the steel preparation process, hot working is not required on the manufactured casting. In other words, the steel in this embodiment may be a cast material (ingot, bloom, or billet). Furthermore, normalizing and / or annealing in accordance with JIS B 6911:2010 "Normalizing and annealing of iron and steel" may be performed on the steel produced in the steel preparation process.
[0087] [(Process 2) Processing process] In the processing step, known processing methods are performed on the manufactured steel material to produce an intermediate product of the member body 30 having the shape described above. The processing methods performed in the processing step include, for example, hot working, cold working, or machining.
[0088] When hot working is performed, the steel material is subjected to hot working to form it into a predetermined shape. After that, the formed intermediate product is allowed to cool to room temperature (air cooling). Hot working is an example of hot forging. The heating temperature in hot working is, for example, 1000 to 1300°C.
[0089] When cold working is performed, the steel material is subjected to a well-known normalizing or spheroidizing annealing process before being cold-worked to form it into a predetermined shape. Cold working is, for example, cold forging.
[0090] Machining may be performed on intermediate products after hot working or cold working. By performing machining, a precise shape that would be difficult to obtain by hot working or cold working alone can be imparted to the stepped annular member 100 of this embodiment. Machining may include cutting or drilling. If the part is a gear, machining may include broaching, for example.
[0091] [(Step 3) Carburizing and quenching process] In the carburizing and quenching process, the manufactured intermediate product is subjected to a carburizing and quenching treatment to form a carburized layer 40 on its surface. The carburizing and quenching process further includes the following steps. (Process 3-1) Carburizing process (Process 3-2) Hardening process The following describes each step.
[0092] [(Process 3-1) Carburizing process] In the carburizing process, the intermediate product is heated and held at a temperature above the austenite transformation temperature in an atmosphere containing a carburizing modified gas with a predetermined carbon potential. Here, the carburizing modified gas refers to a well-known endothermic modified gas (RX gas). RX gas is a gas produced by mixing hydrocarbon gases such as butane and propane with air and reacting them by passing them through a heated Ni catalyst, and is a mixed gas containing CO, H2, N2, etc. In the carburizing process, the carbon potential in the atmosphere is, for example, 0.6 to 1.3%, the heating temperature is, for example, 900 to 1100°C, and the holding time is, for example, 30 to 500 minutes. After the carburizing process, a diffusion process may be carried out. In the diffusion process, the intermediate product is further heated and held in an atmosphere with a predetermined carbon potential. In the diffusion process, the carbon potential in the atmosphere is, for example, 0.6 to 1.3%, the heating temperature is, for example, 800 to 1000°C, and the holding time is, for example, 30 to 500 minutes.
[0093] [(Process 3-2) Hardening Process] In the quenching process, the intermediate product after the carburizing (or diffusion) process is subjected to quenching. Specifically, the intermediate product, after heating and holding, is removed from the heat treatment furnace and rapidly cooled by immersion in an oil bath at 20-180°C.
[0094] The following conditions must be met during the quenching process. (Condition) When the time from immersion of the intermediate product in the oil bath until stirring of the oil bath is started is defined as the non-stirring time t (seconds), the equation (A) is satisfied. 0.080≦(C-0.09) / log(t+1.25)≦0.120 (A) Here, in equation (A), C is substituted with the C content (mass%) of the intermediate product. Also, log means the common logarithm with base 10.
[0095] [Formula (A)] FnA is defined as follows: FnA=(C-0.09) / log(t+1.25) FnA is an index for adjusting the large block area ratio AR in the manufactured stepped annular member 100.
[0096] In general oil quenching, the heated and held steel material is immersed in an oil bath that is being stirred. However, in the manufacturing process of the stepped annular member 100 of this embodiment, the oil bath is not stirred when the intermediate material is immersed in the oil bath. Then, the time until stirring begins is controlled according to the carbon content of the intermediate material. In this way, the large block area ratio AR in the manufactured stepped annular member 100 can be adjusted. The lower the carbon content of the intermediate material, or the longer the non-stirring time t of the oil bath, the more likely it is that hard blocks with a large short-axis width will be generated in the microstructure of the intermediate material after oil quenching. In other words, the lower the FnA in the quenching process, the higher the large block area ratio AR in the manufactured stepped annular member 100.
[0097] If FnA is between 0.080 and 0.120, the large block area ratio AR in the manufactured stepped annular member 100 can be adjusted to 30-75%. Therefore, the carburizing and quenching process should satisfy equation (A). The stirring speed after stirring begins is not particularly limited, as long as it is within a general range considering normal industrial production. The stirring speed is, for example, 100-500 rpm.
[0098] [(Process 4) Tempering process] In the tempering process, the intermediate product after the carburizing and quenching process is subjected to tempering treatment to manufacture the member body 30 that will be provided in the stepped annular member 100. The tempering temperature is, for example, 100 to 200°C. The holding time at the tempering temperature is, for example, 60 to 180 minutes.
[0099] [Other processes] The manufacturing method for the stepped annular member 100 of this embodiment may further include a shot peening process and a finish grinding process.
[0100] [Shot Peening Process] The shot peening process is optional and does not have to be performed. If performed, the shot peening process is carried out on the intermediate product after the carburizing and quenching process. By performing the shot peening process, the retained austenite in the hardened layer of the stepped annular member 100 undergoes a work-induced transformation into martensite. As a result, the volume fraction of retained austenite in the hardened layer decreases. Preferably, the shot peening process uses cut wire or shot particles with a diameter of 1.0 mm or less, with an arc height of 0.3 mmA or more and a coverage of 300% or more.
[0101] [Finishing grinding process] The finish grinding process is optional and does not need to be performed. If performed, the finish grinding process involves performing finish cutting on the intermediate product after the carburizing and quenching process or the shot peening process to improve the surface texture.
[0102] The stepped annular member 100 of this embodiment is manufactured through the above process. [Examples]
[0103] The effects of the stepped annular member of this embodiment will be further explained in detail by the following examples. The conditions in the following examples are just one example of conditions adopted to confirm the feasibility and effects of the stepped annular member of this embodiment. Therefore, the stepped annular member of this embodiment is not limited to this one example of conditions.
[0104] As the material for the stepped annular member, steel materials with the chemical compositions shown in Tables 1A and 1B, corresponding to each test number, were manufactured.
[0105] [Table 1A]
[0106] [Table 1B]
[0107] Specifically, a 100 kg ingot was manufactured by vacuum melting. Hot forging was then performed on the manufactured ingot to produce a 100 mm diameter steel bar. The heating temperature of the ingot before hot forging was 1000-1300°C. The steel bar after hot forging was air-cooled to room temperature.
[0108] Hot forging was performed on the manufactured steel material to produce stepped raw materials. The stepped raw material is a solid raw material for the main body of the component, having a shape in which two cylinders of different diameters are in contact with each other and arranged coaxially. The heating temperature during hot forging was 1200°C. After hot forging, the manufactured stepped raw material was normalized. The normalizing treatment temperature was 925°C, and the holding time at the treatment temperature was 90 minutes. Machining was performed to form a through hole along the central axis. In this way, an intermediate product for the main body of the component to be provided in the stepped annular component was manufactured. In all test numbers, the inner diameter dI of the intermediate product was 40 mm and constant in the axial direction, the wall thickness t1 of the thin-walled section was 5 mm, the axial length h1 of the thin-walled section was 30 mm, and the axial length h2 of the thick-walled section was 20 mm. The ratio of the thickness t2 of the thick section to the thickness t1 of the thin section for each test number was as shown in the "t2 / t1" column of Table 2. The inner circumferential surface of the intermediate product was a smooth circular surface; that is, no splines or other machining were applied to the inner circumferential surface. The shape of the outer circumferential surface in the cross-section of both the thin and thick sections was circular; that is, no teeth were formed on the outer circumferential surface of either the thin or thick section.
[0109] [Table 2]
[0110] The manufactured intermediate samples were subjected to carburizing and quenching. In the carburizing and quenching process, the intermediate samples for each test number were placed in a heat treatment furnace with a carbon potential of 0.90% and heated and held at 920°C for 120 minutes. Subsequently, they were heated and held at 840°C for 30 minutes in the same atmosphere. After the predetermined holding time, the intermediate samples were removed from the heat treatment furnace and immersed in a 60°C oil bath. The oil bath was not stirred at the time of immersion, and stirring was started at a stirring speed of 150 rpm after a period of no stirring time t seconds. The no-stirring time t (seconds) and FnA for each test number are shown in Table 2.
[0111] Tempering was performed on the intermediate samples after carburizing and quenching. Specifically, the intermediate samples were held at 180°C for 120 minutes and then air-cooled to room temperature. In this manner, the main body of each test number was manufactured.
[0112] Stepped annular members for each test number were manufactured using the above process. The carbon concentration at a depth of 100 μm from the surface of the member body for each test number was measured based on the method described in [Method for measuring carbon concentration at a depth of 100 μm from the surface] above. As a result, the carbon concentration at a depth of 100 μm from the surface was 0.60% or higher by mass for all test numbers. In other words, a carburized layer was formed on the surface of the member body for all stepped annular members for all test numbers. Furthermore, the total area ratio of the hard structure in the core for each test number was measured based on the method described in [Method for measuring the microstructure of the core] above. As a result, the area ratio of the hard structure in the core was 95% or higher for all test numbers.
[0113] [Evaluation Test] The following evaluation tests were conducted using the manufactured stepped annular member. (Test 1) Measurement test of the area ratio AR of large blocks (Test 2) Evaluation test for variation in internal diameter deformation The following describes each test.
[0114] [(Test 1) Measurement test of the area ratio (AR) of large blocks] Based on the method described in [Method for Measuring the Large Block Area Ratio AR] above, the large block area ratio AR was measured for the stepped annular member for each test number. The results obtained are shown in Table 2.
[0115] [(Test 2) Evaluation test for variation in internal diameter deformation] Using the stepped annular members of each test number, the degree to which variations in the axial direction of the deformation amount of the inner diameter due to heat treatment strain were suppressed was evaluated by the following method. The stepped annular members for each test number were cut along a cross-section (longitudinal section) that included the central axis. The shape of the resulting longitudinal section was measured, and the maximum (mm) and minimum (mm) values of the inner diameter were determined. Furthermore, the difference between the maximum and minimum values of the inner diameter was calculated, and the resulting value was defined as the variation in inner diameter deformation (mm). The variation in inner diameter deformation (mm) for the stepped annular members for each test number is shown in Table 2. If the variation in inner diameter deformation was 0.035 mm or less, it was determined that the axial variation in the amount of inner diameter deformation due to heat treatment strain was sufficiently suppressed in the stepped annular member for that test number. On the other hand, if the variation in inner diameter deformation exceeded 0.035 mm, it was determined that the axial variation in the amount of inner diameter deformation due to heat treatment strain was not sufficiently suppressed in the stepped annular member for that test number.
[0116] [Test Results] Referring to Tables 1A, 1B, and 2, the stepped annular members of test numbers 1 to 13 had an appropriate chemical composition in the core and a large block area ratio (AR) of 30 to 75%. As a result, the axial variation in the amount of deformation of the inner diameter due to heat treatment strain was sufficiently suppressed.
[0117] On the other hand, in tests 14 and 15, the Fn1 in the chemical composition of the core was too low. As a result, despite the manufacturing conditions being appropriate, the large block area ratio AR was too high. Consequently, the axial variation in the amount of deformation of the inner diameter due to heat treatment strain was not sufficiently suppressed.
[0118] In tests 16 and 17, the Fn1 in the chemical composition of the core was too high. Consequently, despite appropriate manufacturing conditions, the large block area ratio (AR) was too low. As a result, the axial variation in the amount of deformation of the inner diameter due to heat treatment strain was not sufficiently suppressed.
[0119] In tests 18-21, the FnA during the carburizing and quenching process was too low. Consequently, the large block area ratio AR was too high. As a result, the axial variation in the amount of deformation of the inner diameter due to heat treatment strain was not sufficiently suppressed.
[0120] In tests 22-24, the FnA during the carburizing and quenching process was too high. Consequently, the large block area ratio AR was too low. As a result, the axial variation in the amount of deformation of the inner diameter due to heat treatment strain was not sufficiently suppressed.
[0121] As described above, in the member body of the stepped annular member manufactured in this embodiment, no splines or the like were applied to the inner circumferential surface, and no multiple teeth were formed on the outer circumferential surface of the thin-walled portion or the outer circumferential surface of the thick-walled portion. However, even if splines or the like were applied to the inner circumferential surface, or if multiple teeth were formed on at least one of the outer circumferential surface of the thin-walled portion or the outer circumferential surface of the thick-walled portion, the same results as in this embodiment can be obtained. The reason for this is as follows: The surface area of a surface with teeth or grooves increases, which promotes cooling during the quenching process. However, the surface area of the inner circumferential surface of the member body is small in proportion to the total surface area of the stepped annular member. Therefore, the presence or absence of teeth or grooves due to splines or the like applied to the inner circumferential surface has little effect on the variation in the amount of inner diameter deformation. Also, in the case where multiple teeth are formed on at least one of the outer circumferential surface of the thin-walled portion or the outer circumferential surface of the thick-walled portion, in this embodiment, the radial distance from the central axis to the tooth root is defined as the outer radius. When multiple teeth are formed on the outer circumferential surface, the tooth tips are preferentially cooled at the start of cooling, and the cooling of the tooth roots begins later than the tooth tips. As a result, the cooling effect on the outer surface due to the formation of multiple teeth is effectively canceled out. Therefore, the presence or absence of multiple teeth on the outer surface has little effect on the variation in the amount of inner diameter deformation.
[0122] The embodiments of this disclosure have been described above. However, the embodiments described above are merely examples for implementing this disclosure. Therefore, this disclosure is not limited to the embodiments described above, and the embodiments described above can be modified as appropriate without departing from the spirit of this disclosure. [Explanation of Symbols]
[0123] 100: Stepped annular member 30: Main component 10: Thin-walled section 20: Thick wall part 23: Center of the thickest part 40: Carbon-impregnated layer 50: Core X: Central axis
Claims
1. The annular member body comprises an annular thin-walled portion having a wall thickness t1 (mm), and an annular thick-walled portion having a wall thickness t2 (mm) that is coaxial with and in contact with the thin-walled portion and is greater than 1 to 3 times the wall thickness t1, and having a constant inner diameter in the axial direction. The aforementioned member body further, The carburized layer formed on the surface, The region is located inside the carburized layer and includes a core where the total area ratio of the hard structure consisting of martensite and / or bainite is 95% or more. The chemical composition of the core is, in mass%, C: 0.10-0.20%, Si: 0.10-0.80%, Mn: 0.30-2.00%, P: 0.050% or less, S: 0.050% or less, Cr: 0.01-1.50%, Al: 0.010-0.100%, N: 0.005–0.030%, and, O: Contains 0.0030% or less, The remainder consists of Fe and impurities. Satisfying equation (1), At the axial center of the thickened portion, which is located at a depth of t² / ² (mm) radially from the inner circumferential surface, the area ratio of the block of hard tissue with a short-axis width of 2.0 μm or more is 30 to 75%. Stepped annular member. 3.00<Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in equation (1).
2. The annular member body comprises an annular thin-walled portion having a wall thickness t1 (mm), and an annular thick-walled portion having a wall thickness t2 (mm) that is coaxial with and in contact with the thin-walled portion and is greater than 1 to 3 times the wall thickness t1, and having a constant inner diameter in the axial direction. The aforementioned member body further, The carburized layer formed on the surface, The region is located inside the carburized layer and includes a core where the total area ratio of the hard structure consisting of martensite and / or bainite is 95% or more. The chemical composition of the core is, in mass%, C: 0.10-0.20%, Si: 0.10-0.80%, Mn: 0.30-2.00%, P: 0.050% or less, S: 0.050% or less, Cr: 0.01-1.50%, Al: 0.010-0.100%, N: 0.005–0.030%, and, O: Contains 0.0030% or less, Furthermore, it contains one or more selected from the groups consisting of Group 1 to Group 3, The remainder consists of Fe and impurities. Satisfying equation (1), At the axial center of the thickened portion, which is located at a depth of t² / ² (mm) radially from the inner circumferential surface, the area ratio of the block of hard tissue with a short-axis width of 2.0 μm or more is 30 to 75%. Stepped annular member. [Group 1] Mo: 0.50% or less Ti: 0.005% or less, Nb: 0.005% or less, V: 0.15% or less, B: One or more selected from the group consisting of 0.0050% or less. [Group 2] Cu: 0.40% or less, Ni: 0.30% or less, One or more selected from the group consisting of Sn: 0.100% or less. [Group 3] Ca: 0.0050% or less, One or more selected from the group consisting of Mg: 0.0050% or less. 3.00<Mn+3.08Cr<5.00 (1) Here, the content (mass%) of the corresponding element is substituted for each element symbol in equation (1).
3. A stepped annular member according to claim 2, The chemical composition of the core contains the first group, Stepped annular member.
4. A stepped annular member according to claim 2, The chemical composition of the core contains the second group, Stepped annular member.
5. A stepped annular member according to claim 2, The chemical composition of the core contains the third group, Stepped annular member.
6. A stepped annular member according to any one of claims 1 to 5, Multiple teeth are formed on at least one of the outer circumferential surfaces of the thin-walled portion and the outer circumferential surface of the thick-walled portion, along the circumferential direction of the thin-walled portion or the thick-walled portion. Stepped annular member.
7. A stepped annular member according to any one of claims 1 to 5, Spline teeth grooves, keyways, or screw grooves are formed on the inner circumferential surface of the member body. Stepped annular member.
8. A stepped annular member according to claim 6, Spline teeth grooves, keyways, or screw grooves are formed on the inner circumferential surface of the member body. Stepped annular member.
Citation Information
Patent Citations
Gear and manufacturing method for gear
JP2019143211A